INVESTIGATION OF MORAL DISENGAGEMENT IN SPORT AND SPORTSPERSONSHIP BEHAVIOR OF ATHLETES PARTICIPATING IN INTERNATIONAL SPORT ORGANIZATIONS - Halil Erdem Akoğlu; Erdem Ayyıldız; Hakan Sunay (ümit doğan üstün, 2019)
Each branch of sports has its system, rules to be complied with, competition area, and forms. Adopting a sport and wanting to do it requires accepting all its rules from the beginning, obeying them, not opposing them, and defending them. Excessive desire to win which has been created in athletes for various reasons, or existing in the athlete's personality, affects the athlete's departure from sportive morality. The present study aimed to investigate sportspersonship behavior and moral disengagement in the sport of athletes who participated in international sports organizations. The quantitative method was used in the research. Relational screening model, which is one of the general survey models, was used for the purpose. The study group consisted of 164 national athletes who were selected according to non-random sampling methods (criterion sampling method). In order to examine the levels of disengagement from morality in sport, the "The Moral Disengagement in Sport Scale" developed by Boardley and Kavussuan (2008) and adapted to Turkish culture by Gürpınar (2015) was used. The "Multidimensional Sportspersonship Orientation Scale-Msos" developed by Vallerand et al. (1997) and adapted to Turkish by Sezen-Balçikanlı (2010) was used for the study of sportsmanship levels. Demographic variables such as gender, age, educational status, income status, the place where most of his life and sports year were analyzed, and no significant differences were found between disengagement from morality in sport and sportsmanship variables as a result of the analyses. The results of Pearson correlation analysis showed that there was a negative correlation between disengagement from morality in sport and sportsmanship views of individuals. According to the results, sportsmanship behaviors reduced as the levels of disengagement from morality increased. It can be said that the participants generally depend on the responsibilities and social norms in the sport and respect the rules and management. Even though it belongs to the sub-dimension of respect to the lowest average rivals, it was considered positive if it exceeds the average level.